TRANSFORMATIONAL LEADERSHIP IN SUSTAINABLE MANAGEMENT OF PRIMARY SCHOOLS - Boonklam, Ruchanee (Journal of MCU Nakhondhat, 2020)
This academic article was to aims to purpose of studying the transformational leadership of school directors, which affects the administration of the elementary schools in creating sustainability of student development. The target research group used were 798 primary schools under the Office of the Basic Education Commission in Bangkok and suburb area. The informants were 798 school principals. The research instrument was a questionnaire precious an index of consistency with purpose or IOC value of .91 and Reliability value of .89 The statistics for data analysis were the mean, standard deviation, and multiple regression analysis. The results of the study showed that the transformational leadership of the primary school principals overall was at a high level ( = 4.19 , SD = .69), motivation, building a strong team ,creating an Ideological vision and cognitive stimulation respectively and the highest transformational leadership styles was the motivation ( = 4.35, SD = .69), The administration to create sustainability of primary school learner development overall is at a high level ( = 3.92, SD = .71), teaching and learning, development of internal quality assurance systems ,curriculum development and evaluation, respectively. The transformational leadership of the school principals in building strong teams (X4) affects the administration of the primary schools in teaching management (Y2) for sustainability of student development. It is as shown in the equation: ( 2) = 1.985 + 2.015 (X4)